Control Methods for Quadrotor’s Stability - Pang, Shengyuan; Tian, Linzhe (Journal of physics. Conference series, 2021)
Quadrotor unmanned aerial vehicle (UAV) has become more and more popular due to its high maneuverability, vertical take-off, landing and hovering capability, and ease of operation. However, it is subject to various disturbances during the flight, such as turbulence. This paper provides a comprehensive survey of control methods proposed for quadrotor stability. According to the relationship between the controller and the controlled model, this paper divides the quadrotor stability control methods into three categories, namely classical control, optimal control, and intelligent control, for detailed discussion.